2005
DOI: 10.5713/ajas.2005.1464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Probiotic on Growth Performance, Nutrients Digestibility, Blood Characteristics and Fecal Noxious Gas Content in Growing Pigs

Abstract: The aim of this study was to assess the effects of dietary complex probiotic (Lactobacillus acidophilus, 1.0×10 7 CFU/g; Saccharomyces cerevisae, 4.3×10 6 CFU/g; Bacillus subtilis 2.0×10 6 CFU/g) on growth performance, nutrients digestibility, blood characteristics and fecal noxious gas content in growing pigs. Ninety [(Duroc×Yorkshire)×Landrace] pigs with the average initial BW of 39.75±1.97 kg were allocated into three treatments by a randomized complete block design. There were five pens per treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 11 publications
(12 reference statements)
13
58
1
2
Order By: Relevance
“…Thus, dietary supplementation of probiotics indicated few or no significant evidence on pig blood characteristics. In agreement with the current findings, Chen et al (2005), Meng et al (2010), and Lan et al (2016) stated that feeding a probiotic blend to pigs did not influence blood traits. Conversely, it was found that probiotics supplementation in pigs determined an improvement of red blood cells .…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Thus, dietary supplementation of probiotics indicated few or no significant evidence on pig blood characteristics. In agreement with the current findings, Chen et al (2005), Meng et al (2010), and Lan et al (2016) stated that feeding a probiotic blend to pigs did not influence blood traits. Conversely, it was found that probiotics supplementation in pigs determined an improvement of red blood cells .…”
Section: Resultssupporting
confidence: 79%
“…On the contrary, others had negative findings (Quadros et al, 2001). These variable results of the effect of probiotics may be because of aspects such as bacteria strains, level of supplementation, composition of diet, feeding management, feed form and interaction with other dietary additives (Chesson, 1994;Chen et al, 2005;Meng et al, 2010). According to the current results, Česlovas et al (2005) found that probiotics affected meat crude protein amount positively in pigs.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations